Inhibition of Small-Conductance, Ca2+-Activated K+ Current by Ondansetron - Guo, Shuai; Chen, Zhenhui; Chen, Peng-Sheng; Rubart, Michael (Frontiers in Pharmacology, 2021)
Background: Small-conductance Ca2+-activated K+ channels (SK channels) have been proposed as antiarrhythmic targets for the treatment of atrial fibrillation. We previously demonstrated that the 5-HT3 receptor antagonist ondansetron inhibits heterologously expressed, human SK2 (hSK2) currents as well as native cardiac SK currents in a physiological extra- / intracellular [K+] gradient at therapeutic (i.e., sub-micromolar) concentrations. A recent study, using symmetrical [K+] conditions, challenged this result. The goal of the present study was to revisit the inhibitory effect of ondansetron on hSK2-mediated currents in symmetrical [K+] conditions. Experimental Approach: The whole-cell patch clamp technique was used to investigate the effects of ondansetron and apamin on hSK2-mediated currents expressed in HEK 293 cells. Currents were measured in symmetrical [K+] conditions in the presence of 100 nM [Ca2+]o. Results: Expression of hSK2 produced inwardly rectifying whole-cell currents in the presence of 400 nM free cytosolic Ca2+. Ondansetron inhibited whole-cell hSK2 currents with IC50 values of 154 nM and 113 nM at -80 mV and 40 mV, respectively. Macroscopic current inhibited by ondansetron and current inhibited by apamin exhibited inwardly rectifying current-voltage relationships with similar reversal potentials (apamin, ~5 mV and ondansetron, ~2 mV). Ondansetron (1 M) in the continuing presence of apamin (100 nM) had no effect on hSK2-mediated whole-cell currents. Wild-type HEK 293 cells did not express ondansetron- or apamin-sensitive currents. Conclusion: Ondansetron in sub-micromolar concentrations inhibits hSK2 currents even under altered ionic conditions.